Pengaruh Berbagai Jenis Pupuk Daun Terhadap Pertumbuhan Bibit Phalaenopsis sp Asal Kultur Jaringan - Dzulianningsih, Saulifah; Listiawati, Agustina; Asnawati, Asnawati (Fakultas Pertanian Universitas Tanjungpura, 2019)
PENGARUH BERBAGAI JENIS PUPUK DAUNTERHADAP PERTUMBUHAN BIBIT Phalaenopsis spASAL KULTUR JARINGAN Saulifah Dzulianningsih*1, Agustina Listiawati2, Asnawati31Budidaya; Universitas Tanjungpura2Budidaya; Universitas Tanjungpura3Budidaya; Universitas Tanjungpurae-mail: *1ningsihdzulian@yahoo.com ABSTRACTThe seedling of tissue culture still have low autotrophic activity, in purpose of fulfilling the nutritional needs of the seedling from tissue culture, application of fertilizer is needed. The application of fertilizer on the seeds from tissue culture aims to fulfill the intake of plant nutrient that can boost the growth and development of plants, in the seedling phase the fertilization through the leaves is more effective than the soil fertilizer. This study aims to find the best types of foliar fertilizer on the growth of orchid seeds Phalaenopsis sp from tissue culture. The study was conducted at the shelter house at Nirbaya Street, Kotabaru Village, South Pontianak, Pontianak City for 4 months. It was starting from November 23th, 2017 to March 22th, 2018. The study used a Completely Randomized Design (CRD), consisting of 5 treatment, 5 replicates and each treatment unit consisting of 4 plants. Observational variables included the number of leaves increase, the totally of leaf length increase, the totally of leaf area increase, the number of roots increase, and the totally of root length increase and then environmental observation. Based on the research, it can be concluded that type of effective fertilizer for the growth of orchid seeds Phalaenopsis sp from tissue culture is the application foliar fertilizers of green Hyponex and Gandasil D. Keyword: Foliar Fertilizer, Gandasil D, Hyponex, Phalaenopsis sp Orchid.